1982
DOI: 10.1042/bj2060505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cell density on collagen biosynthesis in fibroblast cultures

Abstract: Characteristic features of collagen metabolism in human skin fibroblasts were studied in relation to cell density. Measuring peptide-bound hydroxyproline we found that collagen synthesis per cell decreased when cultures approached confluency. On the other hand, the relative rate of collagen synthesis (collagen/total protein) was higher in quiescent than in proliferating cultures. With increasing cell density the proportion of type III collagen in comparison with type I was found to be slightly increased. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…This phenomenon can partly be explained by dif ferences in the clinical state of the disease, the anatomical biopsy site, sex and age differences between subjects and by variations in the experimental setting [15,18,19]. It was suggested that fibroblasts from scleroderma lesions may exhibit different susceptibilities to endogenous growth fac tors and that withdrawal of such factors upon culturing would result in removal of the stimulus and so could lead to a disappearance of the activated state of the fibroblasts [20, 21 j.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can partly be explained by dif ferences in the clinical state of the disease, the anatomical biopsy site, sex and age differences between subjects and by variations in the experimental setting [15,18,19]. It was suggested that fibroblasts from scleroderma lesions may exhibit different susceptibilities to endogenous growth fac tors and that withdrawal of such factors upon culturing would result in removal of the stimulus and so could lead to a disappearance of the activated state of the fibroblasts [20, 21 j.…”
Section: Discussionmentioning
confidence: 99%
“…Although Dobak et al [28] recently reported an increased collagen synthesis upon exposure to l,25(OH)2D3, they used subconfluent cultures and examined both proliferation and collagen synthesis simultaneously. We used confluent cultures, as it was sug gested that the relative rate of collagen synthesis was higher in quiescent than in proliferating cultures [19], Further more, in confluent cultures calcitriol did not affect cell numbers. In addition, the behaviour of normal and sclero derma fibroblasts incorporated into collagen lattices was not significantly affected in the presence of calcitriol.…”
Section: Discussionmentioning
confidence: 99%
“…Human embryonic skin fibroplasts [17] and the human fibrosarcoma cells HT-1080 [IS] were those used in previous studies. Smooth muscle cell cultures were established from human aorta and showed the characteristics described elsewhere for rabbit smooth muscle cells [19].…”
Section: Cell Rulturrsmentioning
confidence: 99%
“…Although Aumailley et al [16] reported that proliferating human skin fibroblasts synthesized more radiolabeled peptide-bound hydroxyproline per cell than did confluent cultures, their data were not corrected for the specific activity of intracellular proline and it has been shown, in HFL-1 cells, that proline-specific activity is higher in proliferating than in confluent cells [2]. A disparity, therefore, exists in view of the good correlation between collagen mRNA levels and collagen synthesis on the one hand and the lack of correlation between total poly(A)-rich RNA and protein synthesis on the other.…”
Section: Discussionmentioning
confidence: 99%